Burden of benign prostatic hyperplasia in the Middle East and North Africa Region, 1990–2021 - Saeid Safiri; Fikrettin Şahin; Reza Aletaha; Mark J. M. Sullman; Reza Shekarriz-Foumani; Ali-Asghar Kolahi (BMC Public Health)
Abstract Objective To examine the burden of benign prostatic hyperplasia (BPH) in the Middle East and North Africa (MENA) region from 1990 to 2021 by age and sociodemographic index (SDI). Methods Data were sourced from the Global Burden of Disease (GBD) 2021 database. We analysed the incidence, prevalence, and years lived with disability (YLDs) attributable to BPH across the MENA region and its constituent countries. Results In 2021, the MENA region had an estimated 4.7 million prevalent cases of BPH, with an age-standardised prevalence rate of 2168.6 per 100,000. BPH contributed to 93.6 thousand YLDs, with an age-standardised YLD rate of 42.8 per 100,000. The highest prevalence and incidence rates were observed in Jordan, Qatar, and Iran, while Egypt and Yemen recorded the lowest rates. The burden of BPH was found to increase with age, peaking in the 65–69 age range. Conclusion This study reveals an increasing burden of BPH in the MENA region, primarily due to aging populations. These findings underscore the need for tailored public health policies and strategies to enhance early detection, prevention, and management of BPH, thereby reducing its impact on healthcare systems and individuals.